Model of Preparing of the Future Officers to the Professional Activity in the Process of Studying Professional Disciplines - Yurii Lisnichenko (Pedagogical Discourse, 2017)
The article reveals the essence of the model of preparation of the future officers for professional activity in the course of studying of special disciplines. The specific requirements put forward by scientists to the development of pedagogical models of learning have been described. The attention is focused on the productive factors in the simulation of the process of training of the future officers of the airborne forces to professional activity in the course of studying of special disciplines. The pedagogical approaches of formation of readiness of the future officers for professional careers in the course of studying of special disciplines have been offered. Scientific-pedagogical literature has been analyzed, theoretical bases of training of the future officers to professional activity, peculiarities and structure of their training, the basic characteristics and mechanisms of the relationships and aspects of interaction in a model of preparedness have been theoretically grounded. Using the modeling method, the author developed structural-functional model of preparation of the future officers for professional activity in the course of studying of special disciplines. Its main structural components have been presented and described. Key words: model, future officers, professional activity, professional disciplines, structural components.